2015
DOI: 10.2967/jnumed.115.160465
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Reference Levels of CT Radiation Dose in Whole-Body PET/CT

Abstract: The role of CT in PET/CT imaging includes acquisition techniques for diagnostic, anatomic localization, and attenuation correction purposes. Diagnostic reference levels of the volumetric CT dose index (CTDI vol ) are available for dedicated CT procedures on selected body regions, but similar reference levels for whole-body CT used in PET/CT examinations are limited. This work reports CTDI vol values from sites that conduct whole-body oncologic PET/CT examinations and participated in the scanner validation prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…This systematic review focused on the description of different applications of CT scans in PET/CT exams; it included 24 articles for a total of 2948 patients and two papers containing large multicentre studies for comparing the results [7,35] as shown in Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review focused on the description of different applications of CT scans in PET/CT exams; it included 24 articles for a total of 2948 patients and two papers containing large multicentre studies for comparing the results [7,35] as shown in Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…The first paper used for the comparison of our results was made by Fahey et al [7] and focused their work on the dosimetric aspects of paediatric PET/CT exams. The second work, conducted by Jallow et al [35], described diagnostic reference levels of CT scans in WB PET/CT studies. Fahey et al [7] argued that no consistent guidelines are available for CT acquisitions in PET/CT, especially when a paediatric PET/CT exam was involved; in addition to this, they discussed the variability of this study protocol using 19 North American paediatric institutions.…”
Section: Discussionmentioning
confidence: 99%
“…CTDI vol 75 th percentile of whole-body oncological PET/CT protocols submitted to the Society of Nuclear Medicine and Molecular Imaging Clinical Trials Network ranged from 9.7 to 10.2 mGy [24]. The wide ranges of CT acquisition parameters suggested that CTDI vol reference levels may help to optimize CT protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Published articles reported 18 F‐FDG PET/CT DRL values for the administered activity or CT used for AC and anatomical localization purposes, with few authors reporting both radiation doses . PET/CT DRLs from both radiation sources should be reported to provide suitable guidelines for professionals .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical facilities with a median emergent dose that is higher than the national 75 th percentile dose should consider methods of optimizing their clinical imaging protocols to minimize the radiation doses delivered to the patients. 10 Published articles reported 18 F-FDG PET/CT DRL values for the administered activity [11][12][13][14][15][16][17][18][19] or CT 20,21 used for AC and anatomical localization purposes, with few authors reporting both radiation doses. 6,22 PET/CT DRLs from both radiation sources should be reported to provide suitable guidelines for professionals.…”
mentioning
confidence: 99%